Clinical and epidemiological characteristic of epilepsy in children and teenagers in Tomsk Region - L. S. Krayeva; V. M. Alifirova (Бюллетень сибирской медицины)
The incidence of epilepsy and epileptic syndromes (number of new cases per year in a given population) in children and teenagers of Tomsk Region was 44.10 per 100 000 people, being higher in children (49.60) as compared to teenagers (27.39). The prevalence (number of active cases per unit population) was 3.53 per 1 000 people and differs among regions (from 0.74 to 10.95). Most of patients suffered from symptomatic (45.58%) focal epilepsies with predominantly temporal lobe epilepsies (42.04%). The most common etiologic factors of symptomatic focal epilepsies were hypoxic-ischemic perinatal encephalopathies and developmental brain disorders (15.9%). 24.26% patients were switched to politherapy, and others — to monotherapy. Valproates were most often used drug. Remission was achieved in 49.43%.